Zniszczenie kruche prętów mimośrodowo rozciąganych przy uwzględnieniu pełzania ustalonego - Chrzanowski, M. (Engineering Transactions, 1968)
The time of arising initial fractures in a prismatic rod has been determined on the basis of the brittle failure hypothesis proposed by L. M. Kachanov. The rod is loaded with axial force and bending moment. The rod cross-section has only one axis of symmetry. The relation given by F.K. G. Odquist which described a steady creep has been applied as a physical law. Power series has been used to solve the fundamental set of integral equations of statics. These series describe both the stress distribution and the contour of the rod cross-section.The solution thus obtained required an additional interpolation which has been performed on the basis of the formulae given in [12]. The problem has been also solved on a digital computer and these computations allowed to compare the analytical approximate solutions. A numerical example is given for the stretched rod of triangular cross-section. The calculations has been performed both on the basis of derived formulae and using digital computer.